Sustainable Development, Regional Planning, and Information Management as an Evolving Theme in Waqf Research: A Bibliometric Analysis - Hanim Hj Misbah; Fuadah Johari; Fauzias Mat Nor; Dato' Hasnah Hj Haron; Syahidawati Hj. Shahwan; Zurina Shafii (MDPI, 2024)
Indexed by WOS/Scopus/ERA